The Satisfaction to Government’s Policy on Providing Facilities toDisabled Person in Nakhon Pathom Province (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Study on satisfaction with government policy regarding the provision of facilities for people with disabilities in Nakhon Pathom have a purpose To study the satisfaction of government policy regarding the provision of facilities for people with disabilities in Bangkok. and to study and compare the satisfaction of government policies regarding the provision of facilities for people with disabilities in Nakhon Pathom. Classified according to personal factors It is quantitative research. Sample group used in the study Disabled people from the Disabled Persons Central Registration Database Department of Promotion and Development of Quality of Life for Persons with Disabilities In Nakhon Pathom, there were 400 people. The tool used to collect data was a questionnaire through an online system. By using simple random sampling, statistics were used to analyze the data as follows: 1) finding percentage values 2) finding the mean 3) finding standard deviation 4) hypothesis testing. The study results based on the objectives are as follows: 1) Study of satisfaction with the government’s policy regarding the provision of accessibility facilities for people with disabilities in Nakhon Pathom: The study found that overall satisfaction with the government’s policy on providing accessibility amenities for people with disabilities in Nakhon Pathom is at a high level. 2) Comparative study of satisfaction with the government’s policy regarding the provision of accessibility amenities for people with disabilities in Nakhon Pathom, categorized by individual factors such as gender, age, education level, and occupation: The study revealed that satisfaction with the government’s policy on providing accessibility amenities for people with disabilities in Nakhon Pathom varies among different groups based on gender, age, education level, and occupation, in line with the hypotheses set forth.